NUPA10hd-immortalized and genetically engineered progenitors allow studying dendritic cell immune functions - Samson, Guerric P. B.; Anslinger, Nadine; Legler, Daniel F.; Finke, Daniela (Frontiers in Immunology, 2025)
Dendritic cells (DCs) are sentinels of the immune system and potent professional antigen-presenting cells with the ability to encounter antigens in the periphery, migrate to draining lymph nodes, and activate naive T cells. A major challenge in studying DC biology is the poor efficacy of engineering them and generating stable genetically modified DC subsets for preclinical studies and transplantation purposes. Here, we extend studies on Hoxb8-immortalized progenitor cells, previously documented to differentiate into functional DCs, to another Hox-based strategy, namely, constitutive NUP98Hoxa10HD (NUPA10hd) expression in murine hematopoietic progenitor cells. We show that both NUPA10hd- and Hoxb8-immortalized progenitors give rise to functional DCs in vitro, which are capable of CCR7-driven migration and T-cell priming. In contrast to Hoxb8 progenitors, NUPA10hd progenitors show efficient and stable in vivo differentiation into plasmacytoid DCs (pDCs), conventional DC1s (cDC1s), and cDC2s. Finally, we demonstrate the efficacy of the NUPA10hd system in producing genetically modified DCs, allowing the monitoring of DC–T cell interactions and signaling events in migrating DCs. Collectively, NUPA10hd-immortalized progenitors represent a versatile and effective system for investigating immune functions of wild-type and genetically engineered DCs.